’Filterkatadesmos’: symbiosis between the Greek and Egyptian gods in the Classical and Hellenistic periods - Candido, Maria Regina (Romanitas - Revista de Estudos Grecolatinos, 2021)
The mark of identification about the katadesmoi magic practice that resulted in the elaboration of katadesmoi filters among the Athenians holds traces of their practice during the plague that affected Athens in the middle of the Peloponnesian War. The magic of the katadesmoi has the peculiarity of evoking different deities who control the underworld’s sacred space, called Chthonian gods as Hades, Hermes, Persephone, Cerbero, Charon, and Hecate. They are present in the evocations of the katadesmos filters. The singularity identified in the ritual of the filterkatadesmoi is the emergence of Greek deities interacting with the Egyptian gods, evoked through the spells written in the surface of the lead blades.